KONTRIBUSI INDUSTRI PENGOLAHAN HASIL PERIKANAN TRADISIONAL TERHADAP PENDAPATAN NELAYAN PENGOLAH - Yuliana, Ernik; Indrawati, Endang; Farida, Idha (LPPM Universitas Terbuka, 2007)
Traditional fish processing industries in Muara Angke Jakarta have been involving many labor from the local fishermen or others. This study describes the contributions of many small industry to the labor incomes based on every small industry profit distribution. Survey method had been applied to collect the data. The population are all small traditional fish processing industries in Muara Angke. The samples are chosen based on their product, either salty fish or smoked fish. “Hayami method” was applied to calculate the added value of each small industry. The results of this study shows that salty squid has the highest value added (Rp2167,61/kg) and highest profits (Rp2072,61/kg), Indian mackerel smoked fish gives the highest contributions to labor incomes (Rp663,36/kg). Sardinella salty fish gives the highest profit level, followed by salty squid and salty mackerel scad. Salty stingray and salty Indian mackerel gives high value for labor return. In addition, salty sardinella, salty squid, and salty “lesi” fish have high added value ratio. Salty stingray gives the highest other input contribution, followed by smoked Indian mackerel.